Refractory and Super-Refractory Status Epilepticus in Nerve Agent-Poisoned Rats Following Application of Standard Clinical Treatment Guidelines - Morgan, Julia E.; Wilson, Sara C.; Travis, Benjamin J.; Bagri, Kathryn H.; Pagarigan, Kathleen T.; Belski, Hannah M.; Jackson, Cecelia; Bounader, Kevin M.; Coppola, Jessica M.; Hornung, Eden N.; Johnson, James E.; McCarren, Hilary S. (Frontiers in Neuroscience, 2021)
Nerve agents induce a severe cholinergic crisis that can lead to status epilepticus (SE). Current guidelines for treatment of nerve agent-induced SE only include prehospital benzodiazepines, which may not fully resolve this life-threatening condition. This study examined the efficacy of general clinical protocols for treatment of SE in the specific context of nerve agent poisoning in adult male rats. Treatment with both intramuscular and intravenous benzodiazepines was entirely insufficient to control SE. Second line intervention with valproate initially terminated SE in 35% of rats, but seizures always returned. Phenobarbital was more effective, with SE terminating in 56% of rats and 19% of rats remaining seizure-free for at least 24 hours. The majority of rats demonstrated refractory SE and required treatment with a continuous third-line anesthetic. Both ketamine and propofol led to high levels of mortality, and nearly all rats on these therapies had breakthrough seizure activity, demonstrating super-refractory SE. For the small subset of rats in which SE was fully resolved, significant improvements over controls were observed in recovery metrics, behavioral assays, and brain pathology. Together these data suggest that nerve agent-induced SE is particularly severe, but aggressive treatment in the intensive care setting can lead to positive functional outcomes for casualties.